Quantitative Electroencephalogram in Pediatric Intensive Care Unit in Three Different Clinical Scenarios - Yetimakman, Ayse Filiz; Kiral, Eylem (Journal of Pediatric Epilepsy, 2021)
Although clinical judgement and sedation scales are primarily used in intensive care units (ICUs) to manage sedation, adjunctive data are needed to direct therapy with sedative and hypnotic agents to prevent side effects and long-term sequelae. In this case report, we described three cases where we used quantitative electroencephalogram (qEEG) data in a pediatric ICU (PICU); to manage these specific clinical situations and to identify the limitations of the qEEG data, two patients were admitted for post–cardiac arrest care and the third was admitted for status epilepticus. In post–cardiac arrest patients, qEEG was mainly used for monitoring depth of sedation and drug titration. Unnecessary use of high-drug doses was prevented, and monitoring also helped to guide clinical intervention for the management of seizure activity. In the patient with status epilepticus, qEEG data on burst suppression and depth of sedation were used. In this report, we describe three different cases where we used qEEG data in a PICU, to give insight on the use of data in specific clinical situations and to describe the limitations of the qEEG data monitoring system.
Keywords: pediatric intensive care unit; critical care; consciousness monitors